PENGARUH VARIASI KONSENTRASI KALIUM SULFAT PADA PEMBUATAN KARAGENAN DAN APLIKASI KARAGENAN YANG DIHASILKAN SEBAGAI PENGISI SEDIAAN TABLET - Yova Amijaya Fitri (JURNAL FARMASI GALENIKA, 2018)
Carrageenan is a polysaccharide with an average relative molecular mass above 100 kDa, taken from different species of red seaweed (Rhodophyceae). In Indonesia, carrageenan from seaweed Eeucheuma cottonii has been widely produced by the company and used for food additives and pharmaceuticals. However, carrageenan produced from local industries can only meet the food grade and have not been able to meet the pharmaceutical grade because some parameters have not been met, one of which is the sulfate content of carrageenan which must amount to 15-40%. Therefore, in this study the preparation of carrageenan was carried out by using potassium sulfate with various concentrations to increase the sulfate content of carrageenan. Carrageenan obtained was characterized by functional group, sulfate content, gel strength, viscosity, pH, ash content, drying rate, compressibility, flow rate, particle size distribution and application as tablet filler. From result of research known that the addition of potassium sulphate on carrageenan optimal at concentration 0,4 M giving sulfate content 22,64% with gel strength 74,62 g/cm2. Characteristics of carrageenan resulting from a variation in potassium sulfate concentration of 0.2; 0.4 and 0.6 met the expected criteria for pharmaceutical grade. Based on the results of the evaluation tablet known that the resulting tablet has a uniformity of size, uniformity of weight, tablet hardness, friability, friksibility and disintegration time that meets the requirements. Key Word : carrageenan, potassium sulfat, diluent